Respon Bunga Matahari (Helianthus annuus L.) Terhadap Lebah (Aphis cerana) dan Populasi Tanaman - Maryati Maryati (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Response of Sunflower (Helianthus annuus L.) Pollination to Honey Bees (Aphis cerana) and Crop PopulationABSTRACT. High percentage of empty seed most problem sunflower cultivation in Indonesian, less native pollinators may be caused. Grown sunflower in the beekeepers state can be raising sum of fully seeds per head, in the other hand sunflower crops was source of nectar and pollen. The objective of this research was study response of sunflower with expression of percentage of empty seeds and seeds yield to be present honey-bees. The research was conducted in Buanasakti village, Batanghari sub-district, West Lampung district from December 2007 to March 2008. The treatment was distance between beekeepers state (in the stable: 0, 2, and 4 km) and number of plant population per ha (40,000, 60,000, and 80,000 plants). The conclusion was: (1) in the beekeepers state was produce number of branch was higher 124% and 32% than 4 km and 2 km from beekeepers state, respectively: percentage of empty seeds, dry seed per plot and harvest index in the beekeepers state was increasing 199%, 215,47% and 32.36% than 4 km from beekeepers state, (2) The population of 80,000 plant per ha was increasing dry weight of seeds per plot was higher than 60,000 and 40,000 plant per ha, and (3) in each state was difference number of population caused number of flowering date and head diameter prominent was significantly.